1999
DOI: 10.1002/1531-8257(199903)14:2<320::aid-mds1018>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Differential clinical and motor control function in a pair of monozygotic twins with Huntington's disease

Abstract: In the last years the studies regarding the biocompatibility of dental materials investigate, in addition to the classic cytotoxic tests, the interactions between the materials and the host cells to better explain the causes of the adverse effects observed sometimes in the clinical practice. In the present study the ability of diurethane dimethacrylate (DUDMA) and 1,4‐butanediol dimethacrylate (BDDMA) methacrylic monomers present in dental composite resins to alter the functionality of peripheral blood monocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 20 publications
2
56
0
1
Order By: Relevance
“…Therefore, the variable presentations and differing clinical severities suggest a role for an epigenetic environmental influence on the phenotypic presentation of CCHS given the twins' confirmed monozygosity. Similar findings have also been reported in monozygotic twins with Huntington's disease, Marfan syndrome and Moyamoya disease (22)(23)(24).…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, the variable presentations and differing clinical severities suggest a role for an epigenetic environmental influence on the phenotypic presentation of CCHS given the twins' confirmed monozygosity. Similar findings have also been reported in monozygotic twins with Huntington's disease, Marfan syndrome and Moyamoya disease (22)(23)(24).…”
Section: Discussionsupporting
confidence: 88%
“…Although the huntingtin protein was discovered over 10 years ago, its function, regulation, and the mechanisms in pathogenesis are still largely unknown. However, accumulation of cytoplasmic and nuclear aggregates of the mutant huntingtin protein in pathological sites of the brain is believed to play a central role in the pathology of Huntington's disease (DiFiglia et al, 1997); and it has been suggested that both genetic and environmental stress factors could affect huntingtin gene expression, which in turn could impact upon the onset and prognosis of Huntington's disease (Georgiou et al, 1999;Anca et al, 2004;Dixon et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Reduction of normal huntingtin expression, or expression of the polyglutamine track expanded mutant huntingtin proteins, which interact with the normal huntingtin proteins, impairs vesicular and mitochondrial trafficking in mammalian neurons, leading to mitochondrial dysfunction and toxicity (Trushina et al, 2004). Although the regulation of huntingtin gene expression has not been well studied, both genetic and environmental stress factors could affect huntingtin gene expression (Dixon et al, 2004), and that in turn could impact upon the onset and prognosis of Huntington's disease (Georgiou et al, 1999;Anca et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This has been amply illustrated by variation in disease manifestation and onset in monozygotic twins (either reared together or apart) [57][58][59][60][61] and most notably in the Venezuelen kindred 3 . Whilst this adds further complexity to understanding the disease process, it presents an exciting opportunity to impact on the disease course via non-pharmacological means, and without the need to directly modify gene function, which has proved enigmatic to-date.…”
Section: List Of Figuresmentioning
confidence: 99%